Patterns of Pulmonary Function in Patients Undergoing Spirometry at a Tertiary Referral Hospital in West Java, Indonesia - Muhammad Rizky Wisesa; Iceu Dimas Kulsum; Prayudi Santoso (Faculty of Medicine, Universitas Padjadjaran, 2026)
Spirometry is a fundamental tool for assessing pulmonary function, as it provides critical insights into respiratory health. This study aimed to explore pulmonary function abnormalities among patients undergoing spirometry at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Conducted in May 2024 with 206 participants, the study employed a descriptive, observational design. The average patient age was 45.86 years, with a majority being female (64.1%) and unemployed (62.1%). Comorbidities were present in 25.67% of patients, with hypertension being the most common (50.87%). The primary indications for spirometry in this hospital were preoperative risk assessment (75.2%) and evaluation following treatment for multidrug-resistant tuberculosis. The study demonstrated that 67.5% of patients had restrictive lung disorders, 31.6% had normal lung function, and 1% had obstructive patterns. Restrictive lung disorders were more prevalent in older adults and females, with most cases being mild (64.0%). These findings underscore the necessity of spirometry in preoperative assessments, and highlights the dominance of restrictive lung disorders in the hospital’s patient population. Future research should incorporate larger sample sizes, longer study durations, and add additional variables such as respiratory risk factors to enhance understanding of pulmonary function trends in this setting.